2015
DOI: 10.1128/aem.00984-15
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Oxidation of Methane Coupled to Nitrite Reduction by Halophilic Marine NC10 Bacteria

Abstract: Anaerobic oxidation of methane (AOM) coupled to nitrite reduction is a novel AOM process that is mediated by denitrifying methanotrophs. To date, enrichments of these denitrifying methanotrophs have been confined to freshwater systems; however, the recent findings of 16S rRNA and pmoA gene sequences in marine sediments suggest a possible occurrence of AOM coupled to nitrite reduction in marine systems. In this research, a marine denitrifying methanotrophic culture was obtained after 20 months of enrichment. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 41 publications
5
47
0
Order By: Relevance
“…The apparent substrate affinity constants for methane and nitrite were measured in this work, and they were 7.8 ± 1.2 μM and 8.9 ± 2.9 μM, respectively, similar to the results from the previous halophilic NC10 culture (9.8 ± 2.2 μM for methane and 8.7 ± 1.5 μM for nitrite10). The specific cell activity of M. sinica was approximately 0.3 fmol CH 4 day −1 cell −1 in freshwater47 and 0.14 fmol CH 4 day −1 cell −1 in saline water10, higher than that of M. oxyfera (0.09 fmol CH 4 day −1 cell −1 5). It may be explained by the size of the cell; M. sinica is significantly larger than M. oxyfera (0.7–1.2 × 0.7–1.2 μm vs. 0.25–0.5 × 0.8–1.1 μm).…”
Section: Resultssupporting
confidence: 89%
“…The apparent substrate affinity constants for methane and nitrite were measured in this work, and they were 7.8 ± 1.2 μM and 8.9 ± 2.9 μM, respectively, similar to the results from the previous halophilic NC10 culture (9.8 ± 2.2 μM for methane and 8.7 ± 1.5 μM for nitrite10). The specific cell activity of M. sinica was approximately 0.3 fmol CH 4 day −1 cell −1 in freshwater47 and 0.14 fmol CH 4 day −1 cell −1 in saline water10, higher than that of M. oxyfera (0.09 fmol CH 4 day −1 cell −1 5). It may be explained by the size of the cell; M. sinica is significantly larger than M. oxyfera (0.7–1.2 × 0.7–1.2 μm vs. 0.25–0.5 × 0.8–1.1 μm).…”
Section: Resultssupporting
confidence: 89%
“…OTUs listed as potential anaerobic methanotrophs were affiliated with Candidate NC10 (He et al, ) and ANME‐1 (Boetius et al, ; Meyerdierks et al, ). Their relative abundance remained constant with depth at ca.…”
Section: Resultsmentioning
confidence: 99%
“…). However, methane oxidation via NO‐dismutation was only demonstrated for Candidatus Methylomirabilis , the only cultivated member of the candidate phylum NC10 (He et al, ). Taxonomic assignments confirmed the presence of both Candidatus Methylomirabilis and ANME‐1 in the consortia (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the NC10 phylum bacteria were clustered into five different groups, including groups A, group B, group C, group D and group E (He et al . ). The group E, which was not detected in this study, was primarily found to exist in marine environments (He et al .…”
Section: Discussionmentioning
confidence: 97%
“…With the development of molecular biomarkers (the specific primers targeting the 16S rRNA or pmoA genes of M. oxyfera-like bacteria), M. oxyfera-like bacteria of NC10 phylum have been detected in a variety of habitats, primarily including freshwater lake sediments (Deutzmann and Schink 2011; Kojima et al 2012;Deutzmann et al 2014), river sediments (Shen et al 2014a;Zhu et al 2015), estuarine sediments (Shen et al 2014b;Chen et al 2015), marine sediments (Chen et al 2014;He et al 2015), paddy soils (Shen et al 2014c;Zhou et al 2014;Zhu et al 2015) and freshwater wetland soils (Hu et al 2014;Shen et al 2015b,c;Zhu et al 2015). However, because of methodological limitations (e.g.…”
mentioning
confidence: 99%